O cuidado aos usuários com transtorno mental em tratamento com medicação de depósito: as percepções da equipe saúde da família - Jackeline Lourenço Aristides; Brígida Gimenez Carvalho; Dinarte Ballester (2013)
The depot medication has been administered in all family health units inLondrina, in order to increase compliance of users with mental disorder. The objective of this work is to understand the perceptions of family health team in assisting the user who makes use of depot medication. The information was obtained through focus group with these professionals and appreciated by content analysis. It is possible to abstract an improvement after the decentralization of access to this medicine units, but there was no consensus in relation to the increase of autonomy of users after the new therapy. As for deinstitutionalization became evident statements of concern about the socialization of these people. Permeated up lines of alienation and denial about the care provided, as well as statements of lack of infrastructure, human resources and continuing education. It can be seen the necessity of matrix support as a way of coping.